An Air Purifying Herbal Mosquito Repellent Candle with Stress Relief Activity - Pangavhane Ajay Balasaheb; Shaikh Faizan Julfekhar; Bansode Pavan Baban; Ingale Sakshi Ravindra; Giri Mahendra Ashok; Bhalke Rasika Dnyandeo (Asian Journal of Pharmaceutical Research and Development, 2026)
Mosquito-borne diseases such as malaria, dengue, and chikungunya remain major public health concerns worldwide. Conventional synthetic mosquito repellents may produce harmful environmental and health effects, creating the need for safer and eco-friendly alternatives. The present study focuses on the formulation and evaluation of an air-purifying herbal mosquito repellent candle using natural wax, herbal essential oils, and activated charcoal. Neem oil, eucalyptus oil, and lavender oil were incorporated due to their mosquito repellent and aromatic properties, while activated charcoal was added to enhance air purification by adsorbing pollutants and reducing smoke emission.The candle was prepared by melting wax and mixing it with stearic acid, herbal oils, and activated charcoal under continuous stirring. The prepared mixture was poured into molds containing cotton wicks and allowed to cool and solidify. The formulated candle was evaluated for burning efficiency30-60min, Burning rate is 11-12gm/hr and mosquito repellent activity. Burning time was determined using a stopwatch, while mosquito repellency was observed in a closed chamber.The results indicated that the formulated candle possessed good burning characteristics, pleasant aroma, reduced smoke emission, and effective mosquito repellent activity. Activated charcoal contributed to improved air quality and minimized smoke production during burning and weight uniformity was 11gm. The herbal ingredients provided a natural and soothing fragrance along with mosquito protection.The study concludes that the developed herbal mosquito repellent candle is a safe, sustainable, and multifunctional alternative to conventional mosquito control products with additional air-purifying benefits.